Intraspecific variation of the entomophatogenic fungi Beauveria bassiana collected in olive groves from different geographic origin - Coelho, Valentim (2009)
The fungus Beauveria bassiana is a well recognised entomopathogen known to infect hundreds of host species from most of the insect orders. Therefore, the use of this fungus as a biological control agent against insect pests is very promising and several commercial products have already been developed. The natural occurrence of B. bassiana has been reported throughout Spain. Recently, its presence has been also verified in Portugal, specifically in the Trás-os-Montes region.